Executive Function Differences Between First Episode and Recurrent Major Depression Patients - (:unkn) unknown (TURKIYE SINIR VE RUH SAGLIGI DERNEGI, 2010)
Objectives: The differences between recurrent episodes and first episode depression among depressive patients in terms of executive functions had not previously been investigated. In this study, we aimed to explore executive function differences between patient groups with depression and healthy control subjects. Method: 19 first episode sufferers of depression, 14 sufferers of recurrent major depression and 33 healthy subjects, selected as suitable with regard to gender and educational level, were enrolled in this study. In the first session, we applied the SCID-I, State-Trait Anxiety Inventory (STAI), Mini Mental Test (MMT) and the Beck Depression Inventory (BDI). In the second session we applied neuropsychological tests including the Wisconsin Card Sorting Test (WCST), Verbal Fluency Test (VET) and Stroop Tests to all participants. Results: Patients with depression exhibited worse performance in all tests compared to control subjects. While there were no differences between first episode and recurrent depression patients in terms of depression severity and anxiety levels, recurrent depression patients had significantly more perseveration tendency in WCST and significantly worse performance in word production. Among patients in the recurrent depression group, 63,5% had second, 22,2% third, 14,2% had had a fourth episode. There is a significant correlation between the number of depressive episode and the perseveration tendency in WCST. Discussion: The results indicate that, compared to first episode depression, the patients with recurrent depression have worse executive function performance and perseveration tendencies. Episode quantity and perseveration tendency were associated.
Keywords: Recurrent major depression; perseveration; WCST; Verbal Fluency Test; UNIPOLAR DEPRESSION; DYSFUNCTION; DISORDER